Generating specialized interpreters for modular structural operational semantics - Peter Mosses (Logic-Based Program Synthesis and Transformation, 2014)
Modular Structural Operational Semantics (MSOS) is a variant of Structural Operational Semantics (SOS). It allows language constructs to be specified independently, such that no reformulation of existing rules in an MSOS specification is required when a language is extended with new constructs and features.Introducing the Prolog MSOS Tool, we recall how to synthesize executable interpreters from small-step MSOS specifications by compiling MSOS rules into Prolog clauses. Implementing the transitive closure of compiled small-step rules gives an executable interpreter in Prolog. In the worst case, such interpreters traverse each intermediate program term in its full depth, resulting in a significant overhead in each step.We show how to transform small-step MSOS specifications into corresponding big-step specifications via a two-step specialization by internalizing the rules implementing the transitive closure in MSOS and ‘refocusing’ the small-step rules. Specialized specifications result in generated interpreters with significantly reduced interpretive overhead.